Analysis of Students' Pro-Environmental Awareness and Behavior with the AQAL Quadrant at SMA Negeri 1 Medan - Pratama, Alvin; Novira, Nina; Rahmadi, M Taufik; Lubis, Darwin Parlaungan; Elfayetti, Elfayetti (Tunas Geografi, 2025)
Generation Z demonstrates a high level of concern for environmental issues, yet their pro-environmental behavior remains inconsistent. SMA Negeri 1 Medan is recognized as a leading school with adequate facilities, though the level of environmental awareness and behavior among its students is not yet well understood. The use of the AQAL quadrant in analyzing these aspects remains limited, even though this approach can offer a comprehensive analysis across internal and external, as well as individual and collective dimensions. This research aims to analyze the environmental awareness and pro-environmental behavior of students at SMA Negeri 1 Medan. A mixed-methods approach with a sequential explanatory strategy was employed, involving 72 students from grades X and XI. Data were collected through questionnaires, interviews, and observations, then analyzed using the AQAL quadrant approach to integrate quantitative and qualitative findings. The students demonstrated a very high level of environmental awareness (level 5), while their pro-environmental behavior was at a moderate level (level 3), often driven by instructions or competitive activities. The school culture reached a good level (level 4), and the school’s policies strongly supported sustainability (level 5), although consistent implementation by all members of the school community still needs improvement. This indicates that high environmental knowledge, a sustainability-oriented culture, and supportive school policies have not yet significantly translated into consistent pro-environmental behavior among students.